2018
DOI: 10.1038/s41598-018-35980-6
|View full text |Cite
|
Sign up to set email alerts
|

Running in highly cushioned shoes increases leg stiffness and amplifies impact loading

Abstract: Running shoe cushioning has become a standard method for managing impact loading and consequent injuries due to running. However, despite decades of shoe technology developments and the fact that shoes have become increasingly cushioned, aimed to ease the impact on runners’ legs, running injuries have not decreased. To better understand the shoe cushioning paradox, we examined impact loading and the spring-like mechanics of running in a conventional control running shoe and a highly cushioned maximalist shoe a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
40
0
3

Year Published

2019
2019
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 59 publications
(65 citation statements)
references
References 34 publications
6
40
0
3
Order By: Relevance
“…The weight of each subject is a logical feature to consider since the loading rate is expressed as a function of body weight. Furthermore, earlier research has found that footwear properties may affect VILR, even with similar foot-strike patterns (Kulmala et al, 2018). When testing the second cohort (n = 80), the subjects reported their shoe brand and type.…”
Section: Subject-describing Featuresmentioning
confidence: 99%
“…The weight of each subject is a logical feature to consider since the loading rate is expressed as a function of body weight. Furthermore, earlier research has found that footwear properties may affect VILR, even with similar foot-strike patterns (Kulmala et al, 2018). When testing the second cohort (n = 80), the subjects reported their shoe brand and type.…”
Section: Subject-describing Featuresmentioning
confidence: 99%
“…While research has yet to show the superiority of maximalist or minimalist shoes in preventing injuries, it is apparent that various types of footwear cause runners to run differently and shift loads to different body parts. 14 Greater running shoe cushioning tends to increase VLR [15][16][17] and knee joint forces, 18 but decrease ankle forces and peak foot pressure. Conversely, lower cushioning tends to shift initial foot contact closer to the midfoot or forefoot, thus decreasing VLR 19 and knee joint forces, [20][21][22] but increasing ankle forces and foot pressure.…”
Section: Introductionmentioning
confidence: 99%
“…15,25 The rationale for promoting cushioning systems in running shoes is based on the assumptions that external impact forces are associated with injury risk, running on a hard surface is a cause of high-impact forces, cushioning material can reduce these impact forces, and the cushioning itself has no detrimental effect on injury risk. 6 Whereas some scientific evidence suggested that external impact forces were associated with injury risk, 29,39 the influences of shoe cushioning on impact-force characteristics were inconsistent, 25,40,41 as opposed to, for example, running velocity 40 or step rate. 42 This does not exclude a role of shoe cushioning in injury risk, but the active mechanism is most likely not via external impact forces.…”
Section: Shock-absorption Propertiesmentioning
confidence: 99%